Individual and community level risk-factors for alcohol use disorder among conflict-affected persons in Georgia. - Bayard Roberts; Adrianna Murphy; Ivdity Chikovani; Nino Makhashvili; Vikram Patel; Martin McKee (PLoS ONE)
Background The evidence on alcohol use disorder among conflict-affected civilian populations remains extremely weak, despite a number of potential risk-factors. The aim of this study is to examine patterns of alcohol use disorder among conflict-affected persons in the Republic of Georgia. Methods A cross-sectional survey of 3600 randomly selected internally displaced persons (IDPs) and former IDPs. Two alcohol use disorder outcomes were measured: (i) having at least hazardous alcohol use (AUDIT score ≥ 8); (ii) episodic heavy drinking (consuming >60 grams of pure alcohol per drinking session at least once a week). Individual level demographic and socio-economic characteristics were also recorded, including mental disorders. Community level alcohol environment characteristics relating to alcohol availability, marketing and pricing were recorded in the respondents' communities and a factor analysis conducted to produce a summary alcohol environment factor score. Logistic regression analyses examined associations between individual and community level factors with the alcohol use disorder outcomes (among men only). Results Of the total sample, 71% of men and 16% of women were current drinkers. Of the current drinkers (N = 1386), 28% of men and 1% of women were classified as having at least hazardous alcohol use; and 12% of men and 2% of women as episodic heavy drinkers. Individual characteristics significantly associated with both outcomes were age and experiencing a serious injury, while cumulative trauma events and depression were also associated with having at least hazardous alcohol use. For the community level analysis, a one unit increase in the alcohol environment factor was associated with a 1.27 fold increase in episodic heavy drinking among men (no significant association with hazardous alcohol use). Conclusion The findings suggest potential synergies for treatment responses for alcohol use disorder and depression among conflict-affected populations in Georgia, as well as the need for stronger alcohol control policies in Georgia.